High-Resolution Mapping and Biomass Estimation of Suaeda salsa in Coastal Wetlands Using UAV Visible-Light Imagery and Hue Angle Inversion - Lin Wang; Xiang Wang; Xiu Su; Shiyong Wen; Xinxin Wang; Qinghui Meng; Lingling Jiang (Applied Sciences, 2025)
Unmanned Aerial Vehicles (UAVs) have become powerful tools for high-resolution, quantitative remote sensing in ecological and environmental studies. In this study, we present a novel approach to accurately mapping and estimating the biomass of Suaeda salsa using UAV-based visible-light imagery combined with hue angle inversion modeling. By integrating diffuse reflectance standard plates into the flight protocol, we converted RGB pixel values into reflectance and derived hue angle metrics with enhanced radiometric accuracy. A hue angle cutoff threshold of 249.01° was identified as the optimal cutoff to distinguish Suaeda salsa from the surrounding land cover types with high confidence. To estimate biomass, we developed an exponential inversion model based on hue angle data calibrated through extensive field measurements. The resulting model—Biomass = 3.57639 × 10−15 × e0.12201×α—achieved exceptional performance (R2 = 0.99696; MAPE = 3.616%; RMSE = 0.02183 kg/m2), indicating strong predictive accuracy and robustness. This study highlights a cost-effective, non-destructive, and scalable method for the real-time monitoring of coastal vegetation, offering a significant advancement in remote sensing applications for wetland ecosystem management.